1995
DOI: 10.1111/j.1440-1738.1995.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible sub‐arc origin of podiform chromitites

Abstract: The sub-arc mantle condition possibly favors the formation of podiform chromitites.The Cr/(Cr + Al) atomic ratio (= Cr#) of their chromian spinel frequently is higher than 0.7, which js comparable with the range for arc-related primitive magmas. This almost excludes the possibility of their sub-oceanic origin, because both oceanic peridotites and MORB have chromian spinel with the Cr# < 0.6. Precipitation of chromitite and associated dunite enhances a relative depletion of high-field strength elements (HFSE) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…This is consistent with the chemical composition of the primary chromites in the serpentinites and the abundance of chromitites in the area (Robert, 1988;Arai and Abe, 1994;Arai and Yurimoto, 1995;Zhou and Robinson, 1997;Proenza et al, 1999;Matveev and Ballhaus, 2002).…”
Section: Primary Chromite Compositions In Chromitites and Serpentinessupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with the chemical composition of the primary chromites in the serpentinites and the abundance of chromitites in the area (Robert, 1988;Arai and Abe, 1994;Arai and Yurimoto, 1995;Zhou and Robinson, 1997;Proenza et al, 1999;Matveev and Ballhaus, 2002).…”
Section: Primary Chromite Compositions In Chromitites and Serpentinessupporting
confidence: 86%
“…However, the most recent interpretations of the genesis of ophiolitic chromitites suggest a suprasubduction-zone setting. By contrast, no ophiolitic chromitites are thought to form in mature spreading centers, such as mid-ocean ridges (Robert, 1988;Arai and Abe, 1994;Arai and Yurimoto, 1995;Robinson et al, 1997;Schiano et al, 1997;Zhou and Robinson, 1997;Zhou et al, 1998;Proenza et al, 1999;Edwards et al, 2000). From experiments in water-oversaturated basalts, Matveev and Ballhaus (2002) concluded that ophiolitic chromite deposits would form only where there are primitive melts saturated in olivine-chromite and rich in water.…”
Section: Primary Chromite Compositions In Chromitites and Serpentinesmentioning
confidence: 84%
“…Chromite is used as it is often the only unaltered mineral and the composition is believed to represent crystallization compositions (Ahmed et al, 2001;Arai, 1992;Dick and Bullen, 1984;Irvine, 1967), particularly for chromite from lava flows, and within massive chromitite, and dunite. The low diffusivity of Cr, Al, Ti and V within olivine, makes these elements ideal for indicating crystallization compositions (Arai and Yurimoto, 1995). The Cr # indicates the degree of depletion of the mantle source from which the melt was derived, and to a lesser extent, the degree of melt fractionation (Dick and Bullen, 1984;Irvine, 1967Irvine, , 1965.…”
Section: Interpretation Of Chrome Chemistrymentioning
confidence: 99%
“…Alchromite suggest that the Cr-spinel crystallized through high degrees of partial melting at the shallowest levels of an upper mantle source (within the Moho Transition Zone), i.e., close to the layered gabbro sequence (e.g. [60][61][62][63][64][65]). Trace element enrichment of Cs, Rb, Pb, Sb, Sr are caused due serpentinization process, tremolite and/or carbonate precipitation also caused Pb, Sb enrichment and produces in serpentinites (cf.…”
Section: Discussionmentioning
confidence: 99%